The Theory and Practice of Consultation-Liaison (CL) Psychiatry in Trinidad and Tobago with Reference to Suicidal Behavior - Hari D. Maharajh; Petal Abdool; Rehanna Mohammed-Emamdee (The Scientific World Journal)
Consultation-Liaison Psychiatry (CL Psychiatry) is not a well-established discipline in developing countries. It is a multifaceted area that incorporates clinical, teaching, and research activities both within the hospital and extramurally in community health services. Our purpose was first to define the role of CL Psychiatry, to review essential steps in the process, and to advise on how to set up services. Second, a 1-year retrospective analysis was conducted on all patients referred. A total of 708 persons were referred for psychiatric consultation, of which 41% (291) were referred because of suicidal behavior. Sixty-six percent were female and there was an over-representation of Indo-Trinidadians (67%). Twenty-six percent of all cases of suicidal behavior were diagnosed with clinical depression, 3% were suffering from a psychotic illness (schizophrenia), and 8% (24/291) were under the influence of alcohol. The most vulnerable group was the 25- to 35-year-old age group, accounting for 27% (78/291) of attempters, with the largest number of female attempters. The 36- to 55-year-old males were most likely to attempt suicide (35/99). Ingestion of a toxic substance was the most popular method among all races, genders, and age groups. Of all referrals, 95% originated from medical wards. The most common reason cited for attempts was depressed mood, secondary to a domestic dispute with a family member or significant other. Among Caribbean countries, Trinidad and Tobago has high rates of suicide and suicidal behavior, depression, and alcoholism. CL psychiatrists have a major role to play in the delivery of services to these groups, facilitating the transition of care from admission in the emergency room to discharge and follow-up in the community.